Artisanal and small-scale mining and rural livelihood diversification: The case of manganese extraction in West Timor, Indonesia. Issue 1 (January 2019) - Fisher, Rohan; Ling, Hannah; Natonis, Remi; Hobgen, Sarah; Kaho, Norman Riwu; Mudita, Wayan; Markus, Jenny; Bunga, Wida; Nampa, Wayan
Highlights: An estimated 325, 000 rural people actively engaged in mining throughout West Timor during the peak period from 2009 to 2011. Manganese mining was shown to often complement farming practices and contribute to livelihood diversification. Environmental impacts from community mines were not large and could be further reduced with more focused rehabilitation. There is an opportunity to develop best practice outcomes in ASMM through more strategic support. Abstract: This article examines the role of ASM in supporting livelihood diversification, drawing on experiences from subsistence farmers mining manganese in West Timor, Indonesia. An artisanal manganese mining boom, beginning around 2007–2008, in West Timor caused considerable concern amongst government and NGOs. However, unlike ASM gold in Indonesia, there have been no significant assessments of manganese mining to provide a foundation for understanding the impacts of this activity. This study addresses the gap in knowledge regarding the extent, practice, impacts and livelihood contribution of manganese mining in West Timor, Indonesia. The results found artisanal manganese mining to be a significant rural livelihood activity with an estimated 325, 000 people actively engaged in mining over a wide area during the peak period from 2009–2011. Despite the scale of the industry, negative impacts of mining were found to be minimal. Moreover, manganese mining was shown to often complement farming practices and contribute to livelihood diversification. These findings reiterate the call for ASM to be supported by national and international rural development agendas as a valuable and legitimate rural livelihood.